Antimicrobial metal-based nanoparticles: a review on their synthesis, types and antimicrobial action - Guerrero Correa, Matías; Martínez, Fernanda B; Vidal, Cristian Patiño; Streitt, Camilo; Escrig, Juan; de Dicastillo, Carol Lopez (Beilstein journal of nanotechnology, 2020)
The investigation of novel nanoparticles with antimicrobial activity has grown in recent years due to the increased incidence of nosocomial infections occurring during hospitalization and food poisoning derived from foodborne pathogens. Antimicrobial agents are necessary in various fields in which biological contamination occurs. For example, in food packaging they are used to control food contamination by microbes, in the medical field the microbial agents are important for reducing the risk of contamination in invasive and routine interventions, and in the textile industry, they can limit the growth of microorganisms due to sweat. The combination of nanotechnology with materials that have an intrinsic antimicrobial activity can result in the development of novel antimicrobial substances. Specifically, metal-based nanoparticles have attracted much interest due to their broad effectiveness against pathogenic microorganisms due to their high surface area and high reactivity. The aim of this review was to explore the state-of-the-art in metal-based nanoparticles, focusing on their synthesis methods, types, and their antimicrobial action. Different techniques used to synthesize metal-based nanoparticles were discussed, including chemical and physical methods and “green synthesis” methods that are free of chemical agents. Although the most studied nanoparticles with antimicrobial properties are metallic or metal-oxide nanoparticles, other types of nanoparticles, such as superparamagnetic iron-oxide nanoparticles and silica-releasing systems also exhibit antimicrobial properties. Finally, since the quantification and understanding of the antimicrobial action of metal-based nanoparticles are key topics, several methods for evaluating in vitro antimicrobial activity and the most common antimicrobial mechanisms (e.g., cell damage and changes in the expression of metabolic genes) were discussed in this review.